Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.15
|View full text |Cite
|
Sign up to set email alerts
|

Assignment Mechanisms under Distributional Constraints

Abstract: We generalize the serial dictatorship (SD) and probabilistic serial (PS) mechanism for assigning indivisible objects (seats in a school) to agents (students) to accommodate distributional constraints. Such constraints are motivated by equity considerations. Our generalization of SD maintains several of its desirable properties, including strategyproofness, Pareto optimality, and computational tractability while satisfying the distributional constraints with a small error.Our generalization of the PS mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…This approach works if there are upper quotas on agent-object groups that form a bihierarchical constraint structure; it does however not extend to lower quotas on agent-object groups or constraint structures that do not form a bihierarchy. Ashlagi et al (2019b) consider probabilistic allocation with lower and upper bounds on the types of students for each school without priorities and give a suitable generalization of the probabilistic serial. Our model captures the constraints considered by Budish et al (2013), Fujishige et al (2018), andAshlagi et al (2019b), which are all specified by lower and upper quotas or submodular constraints.…”
Section: Extensions Of Probabilistic Serial Without Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach works if there are upper quotas on agent-object groups that form a bihierarchical constraint structure; it does however not extend to lower quotas on agent-object groups or constraint structures that do not form a bihierarchy. Ashlagi et al (2019b) consider probabilistic allocation with lower and upper bounds on the types of students for each school without priorities and give a suitable generalization of the probabilistic serial. Our model captures the constraints considered by Budish et al (2013), Fujishige et al (2018), andAshlagi et al (2019b), which are all specified by lower and upper quotas or submodular constraints.…”
Section: Extensions Of Probabilistic Serial Without Prioritiesmentioning
confidence: 99%
“…Ex ante constraints can include imposing ex ante stability requirements that a system designer may want to impose on the outcome. In that case, a probabilistic allocation is feasible if it satisfies the ex ante constraints and can be decomposed into deterministic allocations that meet the ex post constraints (see, for example, Ashlagi, Saberi, and Shameli, 2019b;Akbarpour and Nikzad, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Irving and Manlove (2010) consider the problem of finding stable matchings with maximum cardinality when priorities have ties, which is known to be an NP-hard problem, and present heuristics for finding them. Ashlagi et al (2020) also consider object assignment problems under distributional constraints. The authors show that variants of serial dictatorship and Probabilistic Serial (Bogomolnaia and Moulin, 2001) mechanisms assign at least as many agents as one can match under the constraints, while the violations of the constraints are relatively small.…”
Section: Related Literaturementioning
confidence: 99%
“…Katta and Sethuraman (2006) showed that when agents are allowed to report indifferences in their preferences, there is no mechanism which is ordinally efficient, envy-free, and weakly strategy-proof. In a recent work, Ashlagi et al (2020) consider the assignment of students to schools under distributional constraints, where each school imposes quotas on subsets of students according to their type. They generalise the PS mechanism based on the same underlying principle of appropriately restricting the menu offered to students, and show that there is no ordinally efficient, within-type envy-free and weakly strategy-proof mechanism in their setting.…”
Section: Introductionmentioning
confidence: 99%
“…They generalise the PS mechanism based on the same underlying principle of appropriately restricting the menu offered to students, and show that there is no ordinally efficient, within-type envy-free and weakly strategy-proof mechanism in their setting. With respect to Ashlagi et al (2020), we may treat the problem with upper and lower quota on objects as a middle ground between the classical random assignment problem and the random assignment problem with distributional constraints. It is therefore interesting to see that albeit we introduce significant constraints, the positive result of the existence of an ordinally efficient, envy-free, and weakly strategy-proof mechanism is retained.…”
Section: Introductionmentioning
confidence: 99%